A look in scientific investigation about Covid-19 and its effects in the education of Perú - Rojas Flores, Segundo Santiago (2021)
Abstract This article reviews publicated articles about the effects of Covid-19 in the education in Perú. First, we describe the current state of research about the effects of the pandemic in different educational stakeholders contextualize the differents challenges that they have taken up. Front he 11 articles found, it can be concluded that there are several effects in the country: the great challenge of e-learning for all, connectivity problems coupled with a lack of adequate equipment for virtual clases, increasing inequality in access to education at all levels and psychological effects of the pandemic, essentially with emotional problems. Keywords: Education; Covid-19; virtual education; pandemic; lockdown; Information and Comunications Technology; psychological impacts.